On the economic and health impact of the COVID-19 shock on Italian regions: A value chain approach - Tommaso Ferraresi; Leonardo Ghezzi; Fabio Vanni; Alessandro Caiani; Mattia Guerini; Francesco Lamperti; Severin Reissl; Giorgio Fagiolo; Mauro Napoletano; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
In this work, we evaluate the exposure of Italian regions to the risk associated with the spread of COVID-19 through a two-step value chain approach. First, we estimate the degree of participation of Italian regions in a plurality of value chains linked to consumption, investment and exports. We distinguish between value chains aimed at satisfying essential needs and supply chains activated by needs characterized by a lower level of necessity in line with the restriction measures implemented by the Italian government. Second, we investigate the different levels of contagion risk associated with each value chain and the possibility of reducing it through remote working. An exercise on policy measures implemented by the Italian government during Fall 2020 completes the paper. We find that regions are affected differently by lockdown policies because of their high heterogeneity in the degree of embeddedness within different value chains and because their sectoral contributions to each of them. As a result, Italian regions are associated with very diverse potentials for mitigating contagion risk via remote working practices. Finally, we find evidence that economic and contagion risks positively correlate in non essential value chains, while they are negatively associated in the production of medium-necessity and essential goods and services. In turn, strong lockdowns induce substantially different trade-offs across regions, depending on how regions participate to value chains.
Keywords: R15; R10; 330; COVID-19 lockdown; value chains; input-output models; contagion risk; remote working